THE ROLE OF CRYPTOCURRENCIES IN THE ECONOMY: ADVANTAGES AND DISADVANTAGES - Bilyk, I.I.; Pohyba А.А. (The actual problems of regional economy development, 2023)
This article analyzes the role of cryptocurrencies in the digital economy, describes their advantages and disadvantages, and conducts an analysis of theoretical and practical aspects. The theoretical aspects of cryptocurrencies include their decentralized nature, cryptographic security, and limited supply. These aspects make them attractive to users who value confidentiality, security, and independence from traditional financial institutions. From a practical perspective, cryptocurrencies have gained popularity as an investment tool, and many investors see significant returns. However, their value can be unstable and prone to rapid fluctuations. In addition, their use in everyday transactions is limited, and many merchants and businesses do not yet accept them as a form of payment. Despite these limitations, cryptocurrencies are likely to continue to play a significant role in the digital economy, as they offer unique advantages and benefits over traditional forms of currency. Scientific studies dedicated to the content and characteristics of the cryptocurrency market have been reviewed. Upon analyzing research and publications on this topic, it has been found that the decentralized nature of digital currencies, on the one hand, provides greater transparency and security, while, on the other hand, the absence of regulation can lead to price manipulation and fraud. In addition, the high volatility of many cryptocurrencies makes them risky investments, and prices often fluctuate sharply in short periods of time. Finally, the anonymity provided by some cryptocurrencies has led to their use in illegal activities such as money laundering and illegal drug trafficking. While cryptocurrencies undoubtedly offer some advantages over traditional currencies and payment methods, it is important to consider these potential negatives when assessing their overall usefulness and potential impact on the financial system. The theoretical and applied understanding of the role of virtual digital currencies in the economy has undergone further development, with further outlining of their prospects for drawbacks.